Advances in the pharmacological management of neutropenia in solid tumors: the advent of biosimilars. (3rd May 2021) - Ghidini, Michele; Indini, Alice; Nigro, Olga; Polito, Simona; Rijavec, Erika; Petrelli, Fausto; Tomasello, Gianluca
ABSTRACT: Introduction : Severe neutropenia and infections are potentially life-threatening complications of cytotoxic antineoplastic therapies and often require hospitalization with a severe economic impact. Furthermore, hematological toxicity frequently results in chemotherapy dose reductions and delays that could interfere with disease control. Areas covered : This review provides an overview of granulocyte colony-stimulating factors (G-CSFs) including pegylated molecules, as well as more recent biosimilar G-CSFs, focusing on the toxicity, pharmacokinetics, and efficacy of these compounds. Expert opinion : The administration of hematopoietic growth factors in primary and secondary prophylaxis of neutropenia is a standard supportive care measure. Recently, several biosimilars have been developed. The market for biosimilar agents seems to be increasing over time thanks to their similar effectiveness and safety, compared with their originators, but lower costs.